Penerapan Metode Pembelajararan Rote Learning di Pondok Pesantren Krempyang Nganjuk - Ahmad Saifuddin (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2017)
The boarding community have formed a subculture which is sociological anthropologist is not simply a physical manifestation is a place to learn, with the buildings, the Yellow Book, students and kiai. But also regarding the broad community who live around it and forms a pattern of cultural life, social and religious, which pattern more or less the same as other religious schools nearby. Morality is the key to the formation of the ethos and structure of the social community of the pesantren. Boarding schools have learned methods to the development of quality children, in this case his protégé santri. Study on the application of teaching model rote learning that author stacking is unprecedented and this is indeed only in Nganjuk Krempyang pesatren. The term knows by model rote learning: Tahfidz mandzumah learning methods. In addition to the boarding school Krempyang Tanjunganom. This method according to the Rowntree (1974), was the concept of the learning method of memorization if model Rowntree not done in a relay while tahfidz mandhzumah done in a relay.